ডেটলাইন বাংলাদেশ : নাইন্টিন সেভেন্টিওয়ান : বাংলাদেশের মুক্তিযুদ্ধকালীন রিপোটার্জ সংকলন সিডনি শনবার্গ - শনবার্গ, সিডনি . (Sydney Hillel), 1934-
Collection of reports published during Bangladesh's freedom movement, by Sydney Schanberg, an American journalist with The New York Times.